\(x^4+2x^3+5x^2+4x-1-m=0\)
\(\Leftrightarrow\left(x^2+x\right)^2+4\left(x^2+x\right)-1-m=0\left(1\right)\)
\(đặt:x^2+x=t\ge\dfrac{-\Delta}{4a}=-\dfrac{1}{4}\)
\(\left(1\right)\Leftrightarrow t^2+4t-1-m=0\) có nghiệm trên \([-\dfrac{1}{4};\text{+∞})\)
\(f\left(t\right)=t^2+4t-1=m\)
\(f\left(-\dfrac{b}{2a}\right)=-5\)
\(f\left(-\dfrac{1}{4}\right)=-\dfrac{31}{16}\Rightarrow m\ge-\dfrac{31}{16}\Rightarrow\left[{}\begin{matrix}t=\dfrac{-b}{2a}=-2\Rightarrow x^2+x+2=0\left(vô-nghiệm\right)\left(loại\right)\\\left\{{}\begin{matrix}t1=\dfrac{-4+\sqrt{20+4m}}{2}=-2+\sqrt{5+m}\\t2=\dfrac{-4-\sqrt{20+4m}}{2}=-2-\sqrt{5+m}\end{matrix}\right.\end{matrix}\right.\)
\(x^2+x=t1=-2+\sqrt{5+m}\Leftrightarrow f\left(x\right)=x^2+x+2=\sqrt{5+m}\) có nghiệm thuộc \(\left[-1;1\right]\)
\(\Rightarrow f\left(-\dfrac{b}{2a}\right)=\dfrac{7}{4}\)
\(f\left(-1\right)=2;f\left(1\right)=4\)
\(\Rightarrow\dfrac{7}{4}\le\sqrt{5+m}\le4\Leftrightarrow\dfrac{-31}{16}\le m\le11\)
\(x^2+x=t2=-2-\sqrt{5+m}\Leftrightarrow f\left(x\right)=x^2+x+2=-\sqrt{5+m}\)
có nghiệm trên \(\left[-1;1\right]\)
\(x^2+x+2>0\Rightarrow x^2+x+2=-\sqrt{5+m}< 0\left(vô-lí\right)\Rightarrow vô-nghiệm\forall m\)
\(\Rightarrow\dfrac{-31}{16}\le m\le11\) thì pt có nghiệm thuộc \(\left[-1;1\right]\)